2002
DOI: 10.1097/00000542-200204000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning with Hyperbaric Oxygen and Hyperoxia Induces Tolerance against Spinal Cord Ischemia in Rabbits

Abstract: Serial exposure to high oxygen tension induced ischemic tolerance in spinal cord of rabbits. Simple hyperbaricity (2.5 ATA, 21% O2) did not induce ischemic tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
73
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(78 citation statements)
references
References 0 publications
3
73
2
Order By: Relevance
“…For example Esmaili et al showed in an in vivo model of rat regional heart ischemia that 120 or 180 minutes of nearly pure oxygen pretreatment could induce delayed heart ischemic tolerance, [23] but our study demonstrates that in kidney, like the central nervous system, [4,7] it takes longer to make tissue tolerant against ischemiareperfusion damage. In 2007, Bigdeli et al induced delayed rat brain ischemic tolerance after 24 h or 6 days of 4 h/day hyperoxia pretreatment, and Dong et al induced delayed rat spinal cord ischemic tolerance after 5 days of 1h/day hyperoxia pretreatment.…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations
“…For example Esmaili et al showed in an in vivo model of rat regional heart ischemia that 120 or 180 minutes of nearly pure oxygen pretreatment could induce delayed heart ischemic tolerance, [23] but our study demonstrates that in kidney, like the central nervous system, [4,7] it takes longer to make tissue tolerant against ischemiareperfusion damage. In 2007, Bigdeli et al induced delayed rat brain ischemic tolerance after 24 h or 6 days of 4 h/day hyperoxia pretreatment, and Dong et al induced delayed rat spinal cord ischemic tolerance after 5 days of 1h/day hyperoxia pretreatment.…”
Section: Discussioncontrasting
confidence: 65%
“…In 2007, Bigdeli et al induced delayed rat brain ischemic tolerance after 24 h or 6 days of 4 h/day hyperoxia pretreatment, and Dong et al induced delayed rat spinal cord ischemic tolerance after 5 days of 1h/day hyperoxia pretreatment. [7] The underlying mechanisms of hyperoxic and hyperbaric preconditioning are not yet fully understood. It seems that subjecting rats to hyperoxia induces the generation of reactive oxygen species (ROS); therefore, a systemic lowgrade oxidative stress is initiated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hyperbaric oxygen (O 2 ) is also able to mimic ischemic preconditioning and induce neuroprotection against ischemic injury in the animal brain and spinal cord. [9][10][11][12][13] It is hyperoxia, not hyperbaricity, that plays the critical role in the induction of tolerance against ischemic injury in the animal brain 11 and spinal cord. 12 Therefore, we hypothesized that the prolonged inhalation of a high concentration of O 2 would result in a similar effect to preconditioning with hyperbaric O 2 .…”
mentioning
confidence: 99%